Characterization and Expression Analysis of the SABATH Gene Family Under Abiotic Stresses in Cucumber (Cucumis sativus L.) - Xinjie Zhang; Shanyu Li; Yang Zhou; Mengxin Chen; Lisi Jiang; Wei Fu (Plants)
SABATH methyltransferase can methylate small-molecule metabolites of plants to generate different products, and it plays a crucial role in plant growth and development as well as stress response. In this study, 13 SABATH genes distributed on five chromosomes of cucumbers were identified, and the synergistic effects among their domains, gene structures, conserved motifs, phylogenetic relationships, collinearity analysis, cis-acting elements, expression patterns, and plant growth-promoting rhizosphere bacteria (PGPR) were analyzed. The gene structure and conserved motifs of the same group of CsSABATH have similar intron numbers and conserved motifs. We detected 10 cis-elements in the promoter of the CsSABATH gene, indicating that they may be involved in different signaling pathways. qRT-PCR revealed the tissue-specific, drought and salt stress-responsive expression of the SABATH gene in cucumbers. Furthermore, we also verified that the expression level of CsaV3_6G046510 after inoculation with PGPR-GD17 bacteria under drought and salt stress was significantly lower than normal drought and salt dress, indicating that this gene may respond to PGPR and in abiotic stress play an important role. This study provides valuable insights into the molecular characteristics and evolutionary history of the SABATH gene family in cucumbers, laying a foundation for further analysis of the function of the CsSABATH gene in cucumbers.